Intracanopy lighting strategies to improve green bush bean (Phaseolus vulgaris) compatibility with vertical farming - Stoochnoff, Jared; Johnston, Melissa; Hoogenboom, Jennifer; Graham, Thomas; Dixon, Mike (Frontiers in Agronomy, 2022)
Now that multi-tiered plant factories with artificial lighting (PFALs) have demonstrated sufficient proof of concept for leafy green and microgreen production; the next challenge is to determine the optimal environment conditions and horticultural management practices required to produce nutrient-dense plant-based protein (PBP) crops within these advanced controlled environment systems (CES). Sole-source lighting within PFALs is energetically and economically expensive, as such, optimizing light distribution through intracanopy lighting could be a key factor in expanding the number of crops compatible with PFAL production. An ideal PBP PFAL crop will have a compact morphology (height, area, volume), be compatible with low-light environments, be self-pollinating, and have a relatively short life cycle. The objectives of this study were to 1) evaluate a selection of green bush bean cultivars (Phaseolus spp.) within a CES to determine which currently available cultivar is most compatible with PFAL production and 2) determine if the addition of intracanopy LED lighting could further improve cultivar compatibility with PFAL systems. The bush bean cultivar "Bronco" was selected after a 40-day flowering and 60-day fruiting trial for its compact morphology and yield (count, fresh weight). Intracanopy LED lighting trials on “Bronco” demonstrated a reduced shoot height (16%), increased bean count (22%), and increased fresh bean weight (17%) relative to plants produced with overhead lighting alone. While intracanopy lighting improved green bush bean compatibility with PFAL production, the additional light applied within the canopy increased the cost of production.